THE USE OF ANIMATION VIDEO AS A MEDIA IN TEACHING NARRATIVE TEXT - Nurizmawati, Chalifatun; Apriliaswati, Rahayu; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research is intended to answer the problem about how does animation video improve reading comprehension in comprehending language features,finding out factual or detail information and drawing moral value on narrative text to the eighth grade students of SMP N 1 SengahTemila. The writer has conducted a classroom action research. The tools of data collection are observation checklist, field notes and test. On the first cycle until the third cycle the writer used animation video as a media toimprove the students reading comprehension in comprehending language features, finding out the factual or detailinformation and drawing the moral value on narrative text. The writer used animation video by showing print screen picture of the story of animation video and giving unfamiliar words to improve the student’s ability in comprehending language features of narrative text. The writer used animation video by predicting, confirming, having class discussion, and testing activity to improve student’s ability in finding out factual or detailed information. The writer used animation video by reviewing each character and finding out the factual or detailed information to improve student’s ability in drawing moral value of narrative text. On the first cycle the student’s mean score was 52.12. In the second cycle students’ mean score was 75.78. In third cycle the students’ mean score was 76.69. Keywords: Animation video, Narrative text, Reading comprehension. Abstrak: Penelitian ini bertujuan untuk menjawab masalah mengenai apakah video animasi meningkatkan kemampuan membaca dalam memahami fitur bahasa, menemukan informasi nyata dan terperinci, dan mengambil nilai moral dalam teks naratif di kelas delapan SMP N 1 SengahTemila. Penulis menggunakan penelitian tindakan kelas. Alat yang digunakan untuk mengumpulkan data adalah lembar pengamatan, catatan lapangan, dan tes.Pada siklus satu sampai siklus tiga penulis menggunakan video animasi sebagai media untuk meningkatkan pemahaman membaca dalam memahami fitur bahasa, menemukan informasi nyata dan terperinci, dan mengambil nilai moral dalam teks naratif. Penulis menggunakan video animasi dengan aktivitas menunjukkan cetakan gambar dari cerita video animasi dan memberikan kata-kata yang tidak dikenal untuk meningkatkan kemampuan siswa dalam memahami fitur bahasa teks naratif. Penulis menggunakan video animasi dengan aktivitas prediksi, konfirmasi, diskusi kelas, dan test untuk meningkatkan kemampuan siswa dalam menemukan informasi nyata dan terperinci . Penulis menggunakan video animasi dengan aktivitas mengulas kembali masing-masing karakter dan menemukan informasi nyata dan terperinci untuk meningkatkan kemampuan siswa dalam mengambi lnilai moral dari teks naratif. Pada siklus pertama rata-rata perolehan nilai siswa adalah 52.12.Pada siklus kedua rata-rata perolehan nilai siswa adalah 75.78. Pada siklus ketiga rata-rata perolehan nilai siswa adalah 76.69. Kata Kunci: Video animasi, Teks narrative, Pemahaman membaca